Public Authorities and Intermediate Organizations

(untitled) (Département des relations industrielles de l’Université Laval, 1964)
SummaryThe importance of close and harmonious collaboration between public authorities on the one hand, and the various associations, organizations, and institutions established independently of government initiative, and generally called « intermediate bodies », on the other, has always been stressed in Catholic social teaching.Two reasons prompt us to devote our annual Labour Day Message to this basic theme. We wish to set it out in terms as concrete as possible, and to review it in the light of the recent and memorable social encyclicals of the late Pope John XXIII, Mater et Magistra and Pacem in Terris.